Imaging of two samples with a single transmit/receive channel using coupled ceramic resonators for MR microscopy at 17.2 T. (31st August 2020) - Moussu, Marine A.C.; Glybovski, Stanislav B.; Abdeddaim, Redha; Craeye, Christophe; Enoch, Stefan; Tihon, Denis; Kurdjumov, Sergej; Dubois, Marc; Georget, Elodie; Webb, Andrew G.; Belov, Pavel; Ciobanu, Luisa
Abstract : In this paper we address the possibility to perform imaging of two samples within the same acquisition time using coupled ceramic resonators and one transmit/receive channel. We theoretically and experimentally compare the operation of our ceramic dual‐resonator probe with a wire‐wound solenoid probe, which is the standard probe used in ultrahigh‐field magnetic resonance microscopy. We show that due to the low‐loss ceramics used to fabricate the resonators, and a favorable distribution of the electric field within the conducting sample, a dual probe, which contains two samples, achieves an SNR enhancement by a factor close to the square root of 2 compared with a solenoid optimized for one sample. Abstract : The possibility of simultaneous imaging of two samples is theoretically and experimentally studied using coupled resonators. Our ceramic probe is compared with a compact solenoid probe, the standard probe in ultrahigh‐field magnetic resonance microscopy. Due to low‐loss ceramics and a beneficial distribution of the electric field in a conducting sample, a dual probe containing two samples achieves an SNR enhancement by a factor close to the square root of 2 compared with a solenoid optimized for one sample.